STRUKTUR NARATIF DAN NILAI SOSIAL DALAM DONGENG JERMAN HANSEL AND GRETEL DAN DONGENG JERMAN RAPUNZEL: KAJIAN SASTRA BANDINGAN - Syfani Zara Ranzani; Putri Ratih Septariyani; Dyah Hesti Retnaningtyas; Alin Ambarwati (Universitas Hamzanwadi, 2026)
This study aims to analyze the narrative structure and social values in the fairy tales Hansel and Gretel and Rapunzel through a comparative literature approach. The scope of the research includes the identification of narrative functions based on Vladimir Propp’s theory and the exploration of social values using Alan Swingewood’s sociology of literature perspective. This study employed a descriptive qualitative method with content analysis techniques. The data consisted of narrative excerpts from Hansel and Gretel and Rapunzel by the Grimm Brothers, which were analyzed using Vladimir Propp’s theory and Alan Swingewood’s sociology of literature approach. The findings reveal that both fairy tales share similar narrative structures, including an initial situation, villainy, struggle, and a happy ending. However, differences are found in the forms of conflict, character roles, and conflict resolution. Hansel and Gretel emphasizes economic conflict and character independence, while Rapunzel highlights psychological conflict and the process of maturation. In terms of social values, both stories convey love, responsibility, and cooperation, although these values are presented in different contexts. These findings indicate that fairy tales possess universal patterns in representing social realities and can serve as a reference for the development of comparative literature studies and literary analysis.